Synthesis, validation and quality controls of [68Ga]-DOTA-Pentixafor for PET imaging of chemokine receptor CXCR4 expression: Synthesis and CQ of [68Ga]-DOTA-Pentixafor - Sammartano, Antonino; Migliari, Silvia; Scarlattei, Maura; Baldari, Giorgio; Ruffini, Livia (Acta Biomedica Atenei Parmensis, 2020)
Background. Chemokine receptor-4 (CXCR4) is involved in tumor growth and progression in several types of human cancer.Recently, [68Ga]-DOTA-Pentixafor has been assessed as an excellent imaging probe targeting CXCR4-expression using positron emission tomography (PET).Here we report on the entire production cycle of [68Ga]-DOTA-Pentixafor, including quality control development and process validation.Methods. Synthesis of [68Ga]-DOTA-Pentixafor was validated via three independent and consecutive production runs using an automated synthesis system. All validation runs must pass the pre-set quality control (QC) limits. Validation was performed for established QC tests to ensure that methods were reproducible and reliable in routine use. Germanium-68 breakthrough was determined for each sample. Production yield was calculated for each synthesis to assess the performance and efficiency of the radiolabeling process. The quality of the final product was determined by ITLC and HPLC methods after each synthesis.Results. The average ITLC‐measured radiochemical purity was above 98.5% and HPLC‐measured radiochemical purity was 99.86%, 99,83% and 100% in the three validation runs. Germanium breakthrough was 4.8*10-5%, 4.9*10-5% and 4.7*10-5% of total activity, far below the recommended level of 0.001%. Residual ethanol resulted 5.22%, 5.58% and 5.32%V/V; spot of HEPES impurity was not more intense than spot of reference solution (200µg/V). Endotoxin level resulted